58.3k views
1 vote
Pls help me solve:-4(x-1)+6x=34

User Rilwan
by
4.4k points

1 Answer

6 votes

Answer:

x = 15

Explanation:

-4(x-1) + 6x = 34 --- distribute the -4 by multiplying

-4x + 4 + 6x = 34

-4x + 6x + 4 = 34 --- rewrite/group like terms and combine

2x + 4 = 34 --- now you need to isolate the variable x

2x - 4 = 34 - 4 --- subtract 4 from each side

2x = 30 --- divide each side by 2 (inverse operation of multiplication)

x = 15

Then to check, plug in 15 for x:

-4(15-1) + 6x = 34

-60 + 4 + 6x = 34

-56 + 6x = 34

-56 + 56 + 6x = 34 + 56

6x = 90 ---divide each side by 6 (inverse op of multiplication)

x = 15

User Unniverzal
by
5.5k points